Can Emerging Adults’ Dating Psychological Aggression be Explained by Family-of-Origin Psychological Aggression, Emotion Dysregulation, and Drinking? - Dhruve, Deepali M. (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) impacts the lives of millions of individuals; nearly 1 in 4 women and 1 in 7 men report experiencing IPV during their lifetime. Previous studies frequently cite family-of-origin aggression as a risk factor for later experiences with IPV. Research with adults who engage in IPV finds an association with childhood exposure to family violence, but the strength of that association may vary. Psychological aggression often pre-dates more severe IPV and college students are a particular risk group for IPV. Additionally, previous literature has revealed gender differences in response to childhood experiences of family violence. As such, the current study sought to identify factors that explain and moderate risk for dating psychological aggression (DPA) in college adults, and sex differences in those associations. Participants (464 women, 142 men), who were in a current romantic relationship lasting at least 3 months, completed measures of past psychological aggression in the family-of-origin (PAF), current emotion dysregulation, risky drinking, and DPA perpetrated in current dating relationships. Emotion dysregulation mediated the relationship between PAF and current DPA; however, differences among specific types of PAF and sex were noted. Results support an intergenerational transmission of PAF and suggest that parent?child sex dyads influence this process. The findings also provide evidence that higher levels of drinking are associated with increased emotion dysregulation. These results contrast with the alcohol expectancy for stress relief and support public messaging that alcohol use does not relieve stress. Clinical and research implications for prevention of the intergenerational transmission of aggression are discussed.